Pembuatan Lembar Kerja Mahasiswa (Lkm) Penunjang Kegiatan Laboratorium Virtual Pada Mata Kuliah Fisika Inti - Luthfiatul Hasanah; Masril Masril; Hidayati Hidayati (Universitas Negeri Padang, 2018)
This research aim to generate a LKM in nuclear physics course. Laboratory activities is one form of learning that allows students to get learning experience through scientific proccess. Observations made show that in the physics department, in the nuclear physics course there is no laboratory activities yet because of the limitations of tools and materials. Virtual laboratpry activities is a recommended solution based on this situation and some related research before. As a form of learning, laboratory activities require teaching materials to support these activities. Research that conducted is a type of research Research and Development. The research procedure is carried out the ADDIE development research model (Analyze, Design, Development, Implementation, Evaluation). The developed product is validated by the physics lecturer as an expert, and practicality is done by the physics lecturer and student. Based on the results of research that has been done, it is found that the LKM to support the virtual lab activities on radioactive decay topic has a validity value of 92.31 with category very valid, practicality value by lecturers 86.87 with category very practical and practicality value by students 87.73 with category very practical.